FRI0506 High Prevalence of Extracutaneous Manifestations and Comorbidities in 108 Patients with Juvenile Localized Scleroderma. (9th June 2015) - Kienast, A.K.; Foeldvari, I.
Abstract : Background: Juvenile localized scleroderma (jLS) is an orphan disease. Only one large survey looked at the prevalence of extracutaneous involvement (EI), but without a standardised assessment protocol. Objectives: Aim of our study was to assess retrospectively EI and comorbidities (CM) of patients with jLS. Methods: We performed a retrospective chart review of consecutive patients with jLS seen in our centre for paediatric rheumatology from May 1999 until October 2014. We collected information regarding demographics, EI and CM. Results: 108 patients were identified. 85 of them had at least one follow up appointment. Mean time of follow- up of the patients was 36.8 months. Mean disease duration to first visit was 50.4 months (n=101). 70 of the 108 patients (64.8%) patients were female. The subset distribution of jLS (n=108) was 28.7% linear scleroderma of the trunk/limbs and 21.3% linear scleroderma of the head ("en coup the sabre"); 24.1% mixed morphea, 9.3% circumscribed superficial morphea, 8.3% generalized, 7.4% circumscribed deep morphea and 0.9% pansclerotic morphea. Mean age at first visit was 12.6 years and 14 patients were older than 18 years old at the time of their first visit. 46 (43%) of the patients showed extracutaneous manifestations. 47 of the 85 were clinically screened for temporomandibular joint arthritis (TMJ) and 9 (19.1%) showed signs of TMJ- arthritis, of these 9 patients had arthritis on clinical exam, 8 on MRI. 3 patients of 72 (4.2%) who were followed and examined by an ophthalmologist developed anterior uveitis. As clinical consequences of the extracutaneous manifestations 5.5% developed lateral trusion at mouth opening, 4.6% decreased mouth opening, 22.2% contractures and 5.5% restricted joint range in non-TMJ. 13% developed length discrepancy of the effected limb and 5.5% leg dystrophy. No patient developed visual impairment. 49 of the 108 patients showed 43 different comorbidities: 7.4% had juvenile idiopathic arthritis, 0.9% rheumatoid arthritis, 6.5% were diagnosed with allergies and 6.5% of atopic eczema, 4% scoliosis, 3.7% migraine and 1.8% hashimoto-thyreoiditis. Conclusions: This retrospective analysis shows a high incidence of patients with EI like TMJ- arthritis, arthritis and uveitis. We would recommend regular clinical investigations for assessment of arthritis, especially TMJ- arthritis and uveitis at least 6 monthly, as suggested from the PReS Scleroderma working group. The extracutaneous manifestations were most common in linear scleroderma of the trunk/limbs subtype. Disclosure of Interest: None declared